Co-production between Governments, Interest Groups, Private Companies and Citizens - a Case Comparison of Vathorst, Spaanse Polder and Gelderse Vallei - Michiel Kort (European Regional Science Association (ERSA), 2005)
Integrated area development projects and promising alternatives have in common that they surpass the values and possibilities of the individual parties (Burger e.a. 2003; Klijn, 1996). In the end solitary action will lead to resistance of other parties involved (and those interested). The ambition to make use of the promising alternatives requires collective action and co-production. In this paper 'co-production arrangements' in three cases will be explored and compared. The cases that are included in this paper are Vathorst, the development of a new housing area, Spaanse Polder, the restructuring of an industrial area and Gelderse Vallei, the reconstruction of a rural area
Keywords: 330